Crisis Communication Model for The Covid-19 Task Force Team of Muhammadiyah in The Epicentrum Region - Ansar Suherman; Moch Imron Rosyidi; Erwin Rasyid (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2021)
Muhammadiyah as an Islamic missionary organization does not only limit itself to religious activities. For more than a century, this organization has shown its real role by being present in the midst of society in various sectors of life, such as education, health, other humanitarian movements, including Muhammadiyah’s response to the COVID-19 pandemic situation. The objective of this study is to determine the extent of Muhammadiyah’s progress in efforts to prevent the transmission of the Covid-19 pandemic from the perspective of crisis communication and Anthony Giddens’ adaptive structuring, and also to identify the crisis communication model for the COVID-19 Muhammadiyah Task Force Team in the Epicenter area. The method used in this research is a phenomenological approach through data analysis with the Interpretative Phenomenological Analysis technique. This research itself is included in the category of the hermeneutic paradigm. The results showed that there were various communication models implemented by the Covid-19 Muhammadiyah task force team at the central and epicenter regions. Each region has different characteristics, in Makassar, the strength of Kyai (religious Leader) and Muhammadiyah figures to provide education and information is still considered very effective as a form of legitimacy. Meanwhile in Jakarta, an effective communication pattern that implements 1 line of coordination with the central MCCC is implemented so that bias does not occur and creates hoaxes in strengthening the significance of the central government. Coordination and consolidation between various regions at the central MCCC continue to be conducted intensively with the collaboration of the Top-down and Bottom-up systems as a form of domination. Coordination and a wider reach by adopting the system developed by the MCCC need to be implemented so that the outreach of the community does not partially focus on Muhammadiyah citizens in particular.Keywords: Covid-19, crisis communication, Muhammadiyah, task force team ABSTRAKMuhammadiyah sebagai organisasi dakwah Islam tidak hanya membatasi diri hanya pada kegiatan keagamaan. Lebih dari satu abad, organisasi ini telah menunjukkan peran nyatanya dengan hadir di tengah-tengah masyarakat dalam berbagai sektor kehidupan. Seperti pendidikan, kesehatan, gerakan kemanusiaan lainnya, termasuk respon Muhammadiyah dalam situasi pandemi COVID-19. Penelitian ini bertujuan untuk mengetahui sejauh mana kiprah Muhammadiyah dalam upaya pencegahan penularan pandemic Covid-19 dari perspektif komunikasi krisis dan strukturasi adaptif Anthony Giddens. Mengidentifikasi bagaimana model komunikasi krisis Tim Gugus Tugas COVID-19 Muhammadiyah yang berada dalam wilayah Episentrum. Metode yang digunakan dalam penelitian ini yaitu pendekatan fenomenologi melalui analisis data dengan teknik Interpretative Phenomenological Analysis. Penelitian ini sendiri termasuk dalam kategori paradigma hermeneutik. Hasil penelitian menunjukkan bahwa terdapat berbagai macam model komunikasi yang dlakukan Tim gugus tugas Covid-19 Muhammadiyah di pusat dan daerah epicentrum. Setiap daerah memiliki karakteristik yang berbeda, di Makassar kekuatan sosok kyai maupun tokoh muhammadiyah untuk memberikan edukasi dan informasi dinilai masih sangat ampuh sebagai suatu bentuk legitimasi. Sedangkan di Jakarta pola komunikasi efektif yang menerapkan 1 garis kordinasi dengan MCCC pusat dilaksanakan agar tidak terjadi bias dan menimbulkan hoax dalam memperkuat signifikansi dari pusat. Koordinasi dan konsolidasi antar berbagai daerah di dengan MCCC pusat terus dijalankan secara intens dengan kolaborasi sistem Top down dan Bottom up sebagai suatu bentuk dominasi. Koordinasi dan jangkauan yang lebih luas dengan mengadopsi Sistem yang dikembangkan MCCC perlu dijalankan agar jangkauan masayarakat tidak secara parsial berfokus pada warga muhammadiyah saja secara khusus.Kata Kunci: Covid-19, komunikasi krisis, Muhammadiyah, tim gugus tugas